Enantioselective Construction of 3‐Hydroxypiperidine Scaffolds by Sequential Action of Light and Rhodium upon N‐Allylglyoxylamides1. (7th May 2015) - Ishida, Naoki; Nečas, David; Masuda, Yusuke; Murakami, Masahiro
Abstract 3‐Hydroxypiperidine scaffolds were enantioselectively constructed in an atom‐economical way by sequential action of light and rhodium upon N‐allylglyoxylamides. In a formal sense, the allylic CH bond was selectively cleaved and enantioselectively added across the ketonic carbonyl group with migration of the double bond (carbonyl‐ene‐type reaction).